2013
DOI: 10.12775/tis.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

The growing importance of the risk-taking channel in the process of transmitting monetary policy

Abstract: Effectiveness of monetary police depends on proper identification of changes happening in functioning of particular channels which transmit impulses of monetary policy directly into economy. Such changes sometimes limit the importance of certain channels, and sometimes they strengthen other channels, as it occurred in the recent years with risk-taking channels. Globalization, growth of competition, anchoring of low inflation in Western economies, too low economic growth when compared with the issue of unemploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“… the situation and changes both on the domestic and international financial market (Redo & Siemiątkowski, 2017);  on the financial and capital account of the balance of payments (Siemiątkowski, 2016(Siemiątkowski, , 2017;  in the amount, cost and availability of capital on the domestic markets and on foreign ones (Redo, 2017);  in the structure, strength and financial-capital situation of bank sector;  in how the banks' tendency to expand credits varies depending on the changes in the central bank's interest rates;  in the fluctuations of an economic situation (Cieślik et al, 2015;Redo, 2015);  in the market interest rate and the variation therein (Redo, 2013);  in the strength, pace, completeness and asymmetry of pass-through effect of a monetary policy relative to the situation on the domestic loan market;  in the financial-capital situation of business enterprises;  in their dependence on the external sources of funding and the demand for working capital (Siemiątkowski, 2014;Siemiatkowski & Jankowska, 2013);  in their dependence on the bank credit;  in the availability of alternative sources of funding (especially short-term ones);  in the characteristic of monetary policies pursued by respective companies;  in the level of the fixity of prices and in its asymmetry;  in the regime of currency exchange and in its stability (Zablotska, 2013);  and finally, in legal regulations and in the instruments availed of by an economic policy which can either solidify or weaken the efficacy of the cost channel of a monetary policy as well as in all the other factors able to aggravate (or mitigate) the difficulties in accessing the sources of funding business enterprises and/or banks, and thereby to enhance (or weaken) the strength of the impulses of a monetary policy exerting some influence on an economy, while simultaneously decreasing its efficiency (Redo, 2016b). Due to the complexity of economic mechanisms, one is unable to pinpoint all the determining factors of the efficiency of the cost channel.…”
Section: Introductionmentioning
confidence: 99%
“… the situation and changes both on the domestic and international financial market (Redo & Siemiątkowski, 2017);  on the financial and capital account of the balance of payments (Siemiątkowski, 2016(Siemiątkowski, , 2017;  in the amount, cost and availability of capital on the domestic markets and on foreign ones (Redo, 2017);  in the structure, strength and financial-capital situation of bank sector;  in how the banks' tendency to expand credits varies depending on the changes in the central bank's interest rates;  in the fluctuations of an economic situation (Cieślik et al, 2015;Redo, 2015);  in the market interest rate and the variation therein (Redo, 2013);  in the strength, pace, completeness and asymmetry of pass-through effect of a monetary policy relative to the situation on the domestic loan market;  in the financial-capital situation of business enterprises;  in their dependence on the external sources of funding and the demand for working capital (Siemiątkowski, 2014;Siemiatkowski & Jankowska, 2013);  in their dependence on the bank credit;  in the availability of alternative sources of funding (especially short-term ones);  in the characteristic of monetary policies pursued by respective companies;  in the level of the fixity of prices and in its asymmetry;  in the regime of currency exchange and in its stability (Zablotska, 2013);  and finally, in legal regulations and in the instruments availed of by an economic policy which can either solidify or weaken the efficacy of the cost channel of a monetary policy as well as in all the other factors able to aggravate (or mitigate) the difficulties in accessing the sources of funding business enterprises and/or banks, and thereby to enhance (or weaken) the strength of the impulses of a monetary policy exerting some influence on an economy, while simultaneously decreasing its efficiency (Redo, 2016b). Due to the complexity of economic mechanisms, one is unable to pinpoint all the determining factors of the efficiency of the cost channel.…”
Section: Introductionmentioning
confidence: 99%
“…Development of the regulations themselves is necessary. From the point of efficiency of monetary policy's actions towards economy, apart from limiting their pro-cyclical character, studies also show the necessity of stronger quality control, control of flow of assets, more clarity in securitization process as well as weakening the risk-taking tendency of financial institutions which is, paradoxically, increased by regulations (more at Redo 2013). It also must be indicated that the majority of research analyzing the effects of prudential regulations are conducted in highly-developed economies -their financial systems significantly differ from the ones in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…It allows for an overall view on contemporary knowledge about complexity of processes of transmitting impulses of monetary policy into economy and highlights, aside from the traditional channel of interest rates, credit channels and channels of assets prices. It also highlights the importance of the influence of monetary policy on the scope of lending and on the price of marketable assets for economic processes, and also on the effectiveness of transmission mechanisms (scheme 1; Redo 2013). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…This is the result of changes in the last decades in operations of financial markets connected with changes in macroprudential regulations and increasingly lower investment profits relying on interest rates, which not only encourage, but even forced to take bigger investment risk in order to gain the planned profits (Rajan, 2005;Adrian and Shin, 2009;Gambacorta, 2009;Farhi and Tirole, 2009a) and additionally cause the classic moral hazard problem (Altunbas, Gambacorta, Marques and Ibanez, 2010). Observed decade by decade increasingly lower interest rates globally caused significant changes in the tendency of economic entities (including financial institutions) to take the risk, their perception of risk, level of risk in an investment portfolio, pricing of assets, conditions and cost of new capital (Borio and Zhu, 2008).…”
Section: Figure 1 the Value Of Selected Parts Of Global Financial Mamentioning
confidence: 99%